Can we reduce CT scan and hospital costs in children with blunt trauma using four parameters? - Tülin Öztaş; Songül Araç; Salim Bilici (SpringerOpen, 2022)
Abstract Background Blunt trauma is one of the most common causes of admission to the emergency service in childhood. Children with trauma are generally evaluated in emergency services where pediatric and adult patients are together, and difficulties are experienced in managing children exposed to trauma. CT is preferred for quick detection and grading of toracoabdominal, skeleton, and neurological injury in high energy trauma. The present study aims to determine the severity of trauma and whether CT exposure can be reduced and patient cost using four parameters. This study was conducted with 586 pediatric patients exposed to blunt abdominal trauma. The clinical prediction rule consisted of four parameters, including abdominal pain, physical examination findings, aspartate aminotransferase (AST), and chest x-ray (CXR, which was used to predict intraabdominal injury in patients with blunt trauma. Patients with no parameters of the clinical decision rule were considered very low risk, and those with one or more parameters were considered at risk. The hospital cost of the patients with and without clinical decision rule was calculated and compared. Results In our study, according to the four-variable clinical prediction rule, 88.1% of the patients had a very low risk of intraabdominal injury and 11.9% of them were at risk. The sensitivity was 97.3%, specificity 98.2%, and accuracy was 97.4% in very low-risk patients with four variables clinical prediction rule. In the very low-risk patients, the abnormal CT rate was 0.3% and conservative treatment was performed. With the use of four variables, 0.17% of solid organ injuries may be overlooked. In the risk of patients, 2.9% of these patients were abnormal CT findings, while tube thoracostomy was performed in four patients with pneumothorax, conservative treatment was performed in other patients. It was determined that routine computed tomography scan increased the patient cost by 5.5 times. Conclusion Patients exposed to blunt trauma with a very low risk of intra-abdominal injury can be identified with a four-variable clinical prediction rule. According to the four-variable clinical prediction rule, very low-risk patients do not require immediate CT. The hospital costs can be reduced by reducing the CT scan. However, it should be kept in mind that a small proportion of intra-abdominal injuries may be overlooked.